SEMANTIC PECULARITIES OF THE NOUNS WITH ABSTRACT MEANING - Oksana Vovkodav (Scientific Journal of Polonia University, 2022)
The aim of this work is to interpret words with abstract meaning with the help of Cambridge Advanced Learner’s Dictionary & Thesaurus. Foreign linguists have made a significant contribution to ideographic lexicography. The essence of ideography is to determine the range of ideas (concepts, archetypes) and verbal means of their reproduction. Ideographic dictionaries are extremely interesting for scholars because they are convenient for solving a variety of linguistic problems. Linguists identify different ways of interpreting the meaning of foreign vocabulary. Abstract nouns are one of the lexical elements of the English language system. The alphabetical principle of arrangement of tokens is convenient and universal, which does not allow to demonstrate the system of vocabulary. However, lexicographers of explanatory alphabet dictionaries can reproduce certain lexical connections through remarks and references. Methods of linguistic research: general scientific (analysis), methods of theoretical research (from abstract to concrete). "... Taking the Cherneyko’s classification of the nouns as the basis of the research we elicit the most common hyperonyms to generalise the meaning of the definitions.